Speed Control of DC Motors Using Full-Wave Uncontrolled Rectifiers: A Comparative Analysis - Yuda Irawan (Journal of Marine Electrical and Electronic Technology, 2024)
The regulation of DC motor speed can be effectively achieved through a variety of methods, such as adjusting the number of pole pairs, employing external resistance regulators, armature input voltage controllers, vector controllers, voltage converters, as well as utilizing Pulse Width Modulation (PWM) techniques and advanced electronic components. These methods allow for precise control of the motor’s operational parameters, ensuring that the system can be adapted to various industrial and practical needs. For instance, by modifying the motor’s operating conditions, different maximum output speeds can be achieved, making it versatile across different applications. A key aspect of motor speed regulation involves the use of simultaneous control techniques, particularly in cascade speed control systems. This allows for multi-level regulation, which optimizes performance by maintaining a balance between the motor’s speed and load demands. In practice, DC motors offer simplicity in design, making them an attractive option for industrial applications. The ease of acquiring necessary components and the relatively low cost of these systems further enhance their popularity in the field of engineering. Moreover, the wide variety of DC motors available today means they can be tailored to meet the diverse needs of industries ranging from automation to precision machinery. The ability to adjust motor speeds with high efficiency ensures that DC motors are indispensable in driving a wide array of mechanical systems, contributing significantly to operational productivity and system stability.